2013
DOI: 10.1523/jneurosci.3285-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

In vivoStimulus-Induced Vasodilation Occurs without IP3Receptor Activation and May Precede Astrocytic Calcium Increase

Abstract: Calcium-dependent release of vasoactive gliotransmitters is widely assumed to trigger vasodilation associated with rapid increases in neuronal activity. Inconsistent with this hypothesis, intact stimulus-induced vasodilation was observed in inositol 1,4,5-triphosphate (IP3) type-2 receptor (R2) knockout (KO) mice, in which the primary mechanism of astrocytic calcium increase – the release of calcium from intracellular stores following activation of an IP3-dependent pathway – is lacking. Further, our results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
252
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(278 citation statements)
references
References 73 publications
26
252
0
Order By: Relevance
“…The Ca 2+ responses in the neuropil appear to have been larger and more frequent than fast astrocytic Ca 2+ responses as reported by others (34). This disparity raised the possibility that the fast Ca 2+ responses we assigned to astrocytes were in fact fluorescence from the neuropil as has recently been proposed (8). We addressed this question in three ways.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The Ca 2+ responses in the neuropil appear to have been larger and more frequent than fast astrocytic Ca 2+ responses as reported by others (34). This disparity raised the possibility that the fast Ca 2+ responses we assigned to astrocytes were in fact fluorescence from the neuropil as has recently been proposed (8). We addressed this question in three ways.…”
Section: Discussionmentioning
confidence: 64%
“…Astrocytes are ideally situated for controlling activity-dependent increases in CBF because they closely associate with synapses and contact blood vessels with their end-feet (1,6). Whether or not astrocytic Ca 2+ responses develop often or rapidly enough to account for vascular signals in vivo is still controversial (7)(8)(9)(10). Ca 2+ responses are of interest because intracellular Ca 2+ is a key messenger in astrocytic communication and because enzymes that synthesize the vasoactive substances responsible for neurovascular coupling are Ca 2+ -dependent (1,4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 These studies demonstrate that cerebral vasodilation precedes elevations in astrocytic Ca 2+ when NVC is elicited. Further, hyperemic responses remain intact in the absence of inositol triphosphate receptor-mediated Ca 2+ signaling in astrocytes.…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies have shown that inositol-1,4,5-trisphosphate (IP3)-dependent calcium release from the endoplasmic reticulum (ER) is important for astrocyte calcium signaling (Petravicz et al 2008;Nizar et al 2013;Takata et al 2013;Srinivasan et al 2015). We examined the involvement of this pathway in sensory stimulation-evoked astrocyte responses by expressing GCaMP6s in astrocytes from Ip3r2 -/-mice and wild-type (WT) littermate controls (Li et al 2005) and selecting sub-cellular ROIs in the same manner as previous experiments (manual selection for endfeet and somata ROIs and automated detection for processes).…”
Section: Astrocytes From Ip3r2 -/-Mice Also Respond To Sensory Stimulmentioning
confidence: 99%